Pendidikan Akhlak dengan Metode Halaqah di Madrasah Ibtidaiyah Matholi’ul Huda Sokopuluhan - Jumbarsih Jumbarsih; Ulfa Kholipah; Faiqoh Nur Ghoutsiyah; Fatihatur Rohmah Ghufroni; Moh Yusuf Ali; Heny Kusumawati (Journal on Education, 2023)
Moral education is part of the teachings of Islamic education. As we all know that the majority of Indonesian is Muslim. With good moral education, the values ​​of Islamic education teachings can be instilled and implemented in this country. Good moral education will lead the perpetrators to become human beings who have noble character in various lines of life. Because moral education is so urgent, it needs to be studied and compared with Western thinkers. The discussion of what the concept of moral education from al-Ghazali's perspective looks like in comparison with the thoughts of Western figures will be examined more deeply in this article. The existence of this study is expected to contribute perspectives on the concept of moral education that exists today. The purpose of writing this journal is to find out what moral education is like being applied to MI Matholi'ul Huda Sokopuluhan, both in terms of programs, methods and processes. This study uses qualitative research methods, namely field research and literature study. This effort was made to obtain a more real picture regarding moral education in these schools. The research sample used was Madrasah Ibtidaiyah Matholi'ul Huda Sokopuluhan. The results of this study include the program used in moral education at MI Matholi'ul Huda Sokopuluhan is a learning program plus the halqah tarbiyah program, while the moral education method applied is the exemplary method, habituation and praise and the process in moral education is carried out by paying attention to various things, namely moral education to God, to oneself and to others. When the methods, programs and processes operate as they should and optimally, they will give birth to students who have Islamic moral character.